Sogidi sacred grove and the construction of the collective Identity of Awe people, Southwest Nigeria (2017)
Groves are imbued with meanings that define how members of a local community relate with landscape and construct reality that defines their collective identity. This article examines Sogidi sacred grove in the context of the construction of the collective identity of Awe people, southwest Nigeria. Techniques of data collection were participant observation, key informants interviews and focus group discussion. The article establishes that Sogidi sacred grove, Awe, imbued with immense religious-cultural values, constitutes the centre of the „being‟ of Awe people. The grove is perceived as the goddess of fertility and its water, “water of life”, signifies the past, the present, and because of the people‟s belief in her healing powers and ability to give children, she also represents the survival, future and the continuity of the Awe people. Allegiance to common beliefs and values associated with Sogidi contributes in building group solidarity among community members, and defining the people‟s collective identity. Many community activities are conducted at Sogidi site, indicating a sense of communality Sogidi grove invokes in the people. Most of the indigenes maintain that Sogidi grove is a gift of the Supreme Being to the town due to the supernatural powers they associate with the site, and its economic significance.